PENGGUNAAN XILANASE Streptomyces sp. 45 I-3 AMOBIL UNTUK HIDROLISIS XILAN TONGKOL JAGUNG [Immobilization of Extracellular Xylanase from Streptomyces sp. 45 I-3 for Hydrolysis of Corncob Xylan ] - Titi Candra Sunarti; Ferry Mutia; Niken Financia Gusmawati; Yulin Lestari; Anja Meryandini (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2009)
Xylan extraction from corncob is done by using alkaline as solvent. Xylan extraction from corncob could give the yields as 10.9%. One percent of corncob xylan is used as substrate to produce the xylanase, compared to oatspelt xylan. Immobilization of xylanase was performed using 1% EudragitTM S100 solution (w/v), with 5:1 volume ratio of xylanase and 1 % EudragitTM S100 (w/v). Activity of the immobilized xylanase was decreased to 23.97% compared with free xylanase. Immobilized xylanase have optimum pH and temperature at 6.0 and 40°C respectively, have also thermal stability at 30–40°C for an hour. Immobilized xylanase could be reused, but its activity decreased to 52.38% after 3 times application.